Sentencing Based on The Principle of Justice for Victims of Serious Crimes Committed by Minors - Freddy Oslan Parningatan; Kristiawanto Kristiawanto; Maryano Maryano (Advances In Social Humanities Research, 2026)
This article analyzes the paradigm shift in the prosecution of criminal cases under the Electronic Information and Transactions Law (ITE Law), from a retributive-formal orientation toward a restorative-proportional orientation within the Indonesian criminal justice system. The urgency of this study arises from the fact that the implementation of the ITE Law has frequently generated legal issues, including multiple interpretations, the criminalization of expression, and tensions between reputation protection, freedom of expression, and legal certainty. The second amendment to the ITE Law through Law Number 1 of 2024 was explicitly motivated by the need to address interpretive ambiguities and controversies within society, while Constitutional Court Decision Number 105/PUU-XXII/2024 further narrows the interpretation of several important provisions, particularly Article 27A, Article 45 paragraph (4), Article 28 paragraph (2), and Article 45A paragraph (2). This research employs a normative juridical method using statutory, conceptual, case-based, and limited comparative approaches grounded in the principle of restorative justice. The research findings indicate that the prosecution of ITE Law cases can no longer be interpreted merely as the transfer of cases to court after the fulfillment of formal legal elements; rather, it constitutes a substantive selection process that considers victims’ interests, loss recovery, proportionality, social impact, and the protection of constitutional rights. This article contributes by formulating a limited restorative prosecution model for ITE Law cases, namely by providing opportunities for the termination of prosecution based on reconciliation only in cases with interpersonal characteristics, where no serious public harm arises and where the requirements of Prosecutor’s Regulation Number 15 of 2020 are fulfilled.